2014
DOI: 10.1016/j.vaccine.2014.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus (HPV) vaccination and subsequent sexual behaviour: Evidence from a large survey of Nordic women

Abstract: Women who received the HPV vaccine before or at the same age as sexual debut did not subsequently engage more in sexual risk taking behaviour than women who did not receive the HPV vaccine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 28 publications
6
41
0
1
Order By: Relevance
“…In a prior study, nearly half of mothers who had talked to their daughters about the HPV vaccine reported that the vaccine discussion led to a discussion about sex. 35 The results of this study, combined with those of previous studies, 1316,36 suggest that clinicians can reassure parents that HPV vaccination does not lead to riskier sexual attitudes and that in fact the vaccination visit can be utilized by clinicians to promote healthier sexual behaviors.…”
Section: Discussionsupporting
confidence: 59%
“…In a prior study, nearly half of mothers who had talked to their daughters about the HPV vaccine reported that the vaccine discussion led to a discussion about sex. 35 The results of this study, combined with those of previous studies, 1316,36 suggest that clinicians can reassure parents that HPV vaccination does not lead to riskier sexual attitudes and that in fact the vaccination visit can be utilized by clinicians to promote healthier sexual behaviors.…”
Section: Discussionsupporting
confidence: 59%
“…A UK-based study by Bowyer et al 74 demonstrated that there was no association between HPV vaccine uptake and age of sexual debut or sexual activity in adolescent girls, and a Scandinavian study found that women who were vaccinated before or at the same age as sexual debut did not subsequently engage more in sexual risk-taking behaviour than those who did not receive the HPV vaccine. 75 Several studies reported significantly greater levels of HPV disease-related knowledge in individuals who had received the HPV vaccine versus unvaccinated peers. However, the general level of knowledge was reported to be low, and misconceptions were commonplace, with some individuals even confusing HPV and HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The study population in the postvaccination survey has been described previously (Hansen et al, 2014). Briefly, in the Scandinavian countries, all residents are registered in nationwide population registries with a unique personal identification number.…”
Section: Study Populationmentioning
confidence: 99%